El campo expandido de la crítica de arte: análisis discursivo de un debate (2014)
The purpose of this paper is to make a study from the critical in the Esferapublica.org Net and media’s debate written between August 26 and September 23, 2009, about Tania Bruguera’s performance Untitled (Bogotá, 2009). In which the Cuban artist shared with the audience some trays of cocaine; while, three Colombian armed actors were talking about the political hero’s construction. Through this analysis I will establish what kind of criticism is implemented on an alternative mean.